Application of three-dimensional visualization technology in phacoemulsification benefits the dry eye symptoms of patients after cataract surgery - Wu, Chen; Chen, Qingzhong; Zhang, Guangbin (Frontiers in Medicine, 2024)
Purpose To investigate the effects of the three-dimension visualization system on dry eye in patients after cataract phacoemulsification. Methods Seventy-one patients (104 eyes) were enrolled in this study and assigned to the conventional microscopic group (CM group) or three-dimension group (3D group). Ocular Surface Disease Index, The Schirmer I test (SIt), lipid layer thickness (LLT), noninvasive tear breakup time (NIBUT) and other factors associated with dry eye were recorded before and 1 week and 1 month after surgery. The operation time and intraoperative light intensity (ILI) were also recorded. Results The ILI in the 3D group was significantly lower than that in the CM group (33% vs. 60%, p < 0.01). There was an interaction (group and time) effect for first NIBUT (NIBUT-F), average NIBUT (NIBUT-Ave), tear meniscus height (TMH) and the score of eye redness (Pinteraction < 0.05). The main effects of group on SIt, LLT, NIBUT-F, NIBUT-Ave and the score of eye redness were significant (Pgroup < 0.05). In the CM group, SIt, LLT, NIBUT-F, NIBUT-Ave, TMH were lower than those of the 3D group, the score of eye redness was higher than that of the 3D group at 1 week and 1 month after surgery (all p < 0.05). The changes in NIBUT-F and NIBUT-Ave between before surgery and 1 week after surgery showed negative correlations with ILI (p < 0.01). Conclusion Compared with microscopic surgery, the 3D visualization system can provide better tear film stability for patients after cataract surgery.